2015
DOI: 10.1167/15.8.5
|View full text |Cite
|
Sign up to set email alerts
|

How crowding, masking, and contour interactions are related: A developmental approach

Abstract: Young children are characterized by poor visual performances. Visual crowding, lateral interactions, and contour detection are critical functions for visual perception, context effect, and recognition that develop over the years up to maturity. The age at which the maturation's onset of the functions can be observed and the functions' underlying neural basis remain unclear. Here we used a development approach to investigate the onset of the foveal visual functions in order to learn about their neuronal basis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 95 publications
2
26
1
Order By: Relevance
“…26,27 A recent study on crowding in 3-to 15-year-old children with normal vision demonstrated that vision in children younger than 7 years is dominated by suppressive interactions between contours. 28 Crowding can be iovs.arvojournals.org j ISSN: 1552-5783 measured in two different ways: one is the maximum distance at which a distractor causes degraded perception of the target (the extent), and the second is the amount of loss in visual acuity when the interaction is at its maximum (the intensity). 4 The crowding extent is the minimum distance needed between a threshold-size target and flankers to allow target recognition.…”
mentioning
confidence: 99%
“…26,27 A recent study on crowding in 3-to 15-year-old children with normal vision demonstrated that vision in children younger than 7 years is dominated by suppressive interactions between contours. 28 Crowding can be iovs.arvojournals.org j ISSN: 1552-5783 measured in two different ways: one is the maximum distance at which a distractor causes degraded perception of the target (the extent), and the second is the amount of loss in visual acuity when the interaction is at its maximum (the intensity). 4 The crowding extent is the minimum distance needed between a threshold-size target and flankers to allow target recognition.…”
mentioning
confidence: 99%
“…Thus the timeframe in which strabismus exerts its influence on the developing visual system can be inferred. The findings of our study suggest that in strabismic amblyopia, the visual system is affected before the maturation of crowding is complete, at around 6-12 years, depending on the study design (Bondarko & Semenov, 2005;Doron et al, 2015;Jeon, Hamid, Maurer, & Lewis, 2010).…”
Section: Discussionmentioning
confidence: 73%
“…A further explanation for the increased crowding in the amblyopic eyes could stem from the findings of Lev et al (2014), where crowding was shown to be greater where larger perceptive fields are used. In foveal viewing in amblyopic eyes, similar to with young children, larger processing units may be used (Doron et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed BN's contour integration ability using the contour integration card set (Kovacs et al 1999, Doron et al 2015) and compared it to previously published age-typical performance as well as to the group of age-matched controls participating in our study. Each card in the set consists of a round contour made of collinear Gabor patches ("signal") that is embedded in randomly oriented Gabor patches ("noise").…”
Section: Methodsmentioning
confidence: 99%